Current topics in developmental biology. - Pedersen, Roger A.; Schatten, Gerald (Current topics in developmental biology, 1999)
This Series provides a comprehensive survey of the major topics in the field of developmental biology. The volumes are valuable to researchers in animal and plant development, as well as to students and professionals who want an introduction to cellular and molecular mechanisms of development. The Series has recently passed its 30-year mark, making it the longest-running forum for contemporary issues in developmental biology.